The histochemical assessment of sulpho-, sialo-, and neutral-mucosubstances in fetal gastric mucosa - Prasanna, Lokadolalu Chandracharya; Thomas, Huban R.; D’Souza, Antony Sylvan; Bhat, Kumar MR. (International Journal of Research in Medical Sciences, 2017)
Background: Mucins are complex composition of carbohydrates and may be present as a mixture of different types. Normal distribution of mucin and its alteration in various inflammatory, benign and malignant lesions of gastrointestinal tract has aroused interest in the field of histochemistry. The main purpose of present work is to study the staining pattern and distribution of cells in different parts of fetal gastric mucosa and to correlate the nature of gastric mucins and its functional significance. Methods: A total of 25 fetus stomach specimens (total 75 samples) one sample each from different parts of the stomach like fundus, body and pylorus, from fresh specimens. The samples were washed in normal saline, fixed in 2% calcium acetate in 10% formalin. These tissues were routinely processed and paraffin blocks were prepared. 6 m sections of these blocks were taken for histological and different histochemical staining. Results: Fetal fundic part of stomach shows increased neutral mucin in surface epithelium and foveolar cells. With combined AB pH 2.5 - PAS technique increased neutral mucin and small amount of acid mucins are observed. With AB pH 1, surface epithelium and deep glands show negative staining. Moderate alcinophilia is observed in deep foveolar cells and glandular cells. AB pH 2.5 shows alcinophilia in surface epithelium, foveolar cells and mucous neck cells indicating presence of sialomucin. Fetal pyloric part of stomach shows increased acid and neutral mucins. With pH 2.5 - PAS staining, purple staining is observed in surface epithelium, deep foveolar and pyloric glands. Conclusion: All types of mucosubstances - neutral, sialo and sulpho-mucins, are secreted in relatively increased amounts by the surface epithelium and the glands of the stomach of the human fetus and neonate. Sulphomucin is seen mainly in the cells of the surface epithelium.